2017
DOI: 10.1038/jp.2017.31
|View full text |Cite
|
Sign up to set email alerts
|

Success of labor induction for pre-eclampsia at preterm and term gestational ages

Abstract: The majority of women with pre-eclampsia who undergo IOL achieve vaginal birth, even at early GAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 14 publications
1
8
0
1
Order By: Relevance
“…In half of the women, labor was induced, and the remainder underwent cesarean delivery without labor.Induction was successful in accomplishing vaginal delivery in a third. Others have reported similar observations (Roland, 2017 ) [15] . Unfortunately, none of these studies further analyzed the failure causes of vaginal trial.When multiple logistic regression analysis was performed,this study got that cephalopelvic disproportion(OR ¼ 2.13; 95% CI: 1.43-8.13) and fetal distress (OR¼2.42; 95% CI: 1.76-6.65) remained signi cantly associated with transfer-cesarean section,which is consistent with the risk factors of conversion to cesarean section during vaginal delivery in normal pregnant.And it can alleviate the anxiety of obstetricians and pregnants that the maternal and fetal'preeclampsia conditions would worsen during vaginal delivery in some extent .…”
Section: Risk Factors Of Transfer-cesarean Sectionsupporting
confidence: 66%
“…In half of the women, labor was induced, and the remainder underwent cesarean delivery without labor.Induction was successful in accomplishing vaginal delivery in a third. Others have reported similar observations (Roland, 2017 ) [15] . Unfortunately, none of these studies further analyzed the failure causes of vaginal trial.When multiple logistic regression analysis was performed,this study got that cephalopelvic disproportion(OR ¼ 2.13; 95% CI: 1.43-8.13) and fetal distress (OR¼2.42; 95% CI: 1.76-6.65) remained signi cantly associated with transfer-cesarean section,which is consistent with the risk factors of conversion to cesarean section during vaginal delivery in normal pregnant.And it can alleviate the anxiety of obstetricians and pregnants that the maternal and fetal'preeclampsia conditions would worsen during vaginal delivery in some extent .…”
Section: Risk Factors Of Transfer-cesarean Sectionsupporting
confidence: 66%
“…There was no increased risk of CD among women with past placenta-mediated pregnancy complication who underwent induction of labor, compared to spontaneous labor. Our data adds to a reassuring and growing body of literature that suggests there is no increased CD risk based on these indications for induction [12][13][14][15][16] . While our results are not generalizable to a low-risk obstetrical population, they support the results of the randomized ARRIVE Trial that showed a decreased risk of CD among low-risk nulliparous women randomized to induction of labor (18.6% versus 22.2%, RR 0.84, 95% CI 0.76-0.93) 10 , with a difference in CD rates that persisted across the pre-specified subgroups of age, ethnicity, body mass index and modified Bishop score.…”
Section: Discussionmentioning
confidence: 55%
“…Medical indications for induction are heterogeneous, and may influence the risk of CD to varying degrees. Based on a limited number of studies, there is likely no increased risk of cesarean delivery after induction of labor among patients with pre-eclampsia or chronic hypertension, with improved maternal outcomes [12][13][14][15][16] . Women who have a previous history of late pregnancy loss, pre-term birth, or delivery of a small-for-gestational-age (SGA) infant are at increased risk of developing complications such as a stillbirth in a future pregnancy 17 .…”
mentioning
confidence: 99%
“…По поводу этих факторов существуют разные мнения. Одни авторы возраст рожениц старше 35 лет и первые роды [6,7] относят к факторам риска, а другие как раз свидетельствуют об отсутствии связи возраста и наличия родов в анамнезе с риском оперативных родов [8].…”
Section: результаты исследования и их обсуждениеunclassified